2010
DOI: 10.1177/0013916510371754
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Energy Consumption and Creating a Conservation Culture in Organizations: A Case Study of One Public School District

Abstract: How can existing schools significantly reduce their energy use? With energy costs rising and school budgets shrinking, energy use is a substantial cost that can be reduced through conservation efforts. Using a case study methodology, the authors compare two public high schools from the same school district, one that has achieved moderate energy savings and another that has reduced its electricity use by 50% over several years. Examining the individual and organizational components of both schools' efforts, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 37 publications
3
77
0
Order By: Relevance
“…This theory suggests that intention is directly related to behavior, which can be predicted on the basis of attitudes toward the behavior, subjective norms, and perceived behavioral control (Ajzen, 1991;Schelly, Cross, Franzen, Hall, & Reeve, 2011). Using TPB, one could infer that positive intention to conserve electricity should lead to a positive behavioral change.…”
Section: Attitudes Toward Energy Conservationmentioning
confidence: 99%
“…This theory suggests that intention is directly related to behavior, which can be predicted on the basis of attitudes toward the behavior, subjective norms, and perceived behavioral control (Ajzen, 1991;Schelly, Cross, Franzen, Hall, & Reeve, 2011). Using TPB, one could infer that positive intention to conserve electricity should lead to a positive behavioral change.…”
Section: Attitudes Toward Energy Conservationmentioning
confidence: 99%
“…These include individual determinants such as attitudes (; Jones, 1990;Scherbaum, Popovich, & Finlinson, 2008), self-efficacy (Tudor, Barr, & Gilg, 2007), perceived social norms (Nolan, Schultz, Cialdini, Goldstein, & Griskevicius, 2008;Tudor et al, 2007), and behavioral intentions (Jones, 1990). External factors, such as leadership (Conger & Kanungo, 1987;Conger, Kanungo, & Menon, 2000;Schelly, Cross, Franzen, Hall, & Reeve, 2011), organizational culture (Higgs & McMillan, 2006), and campaigns (Schelly et al, 2011;F. W. Siero, Bakker, Dekker, & Marcel, 1996;S.…”
Section: Introductionmentioning
confidence: 99%
“…The few studies that have found evidence of durable behavior changes, even after interventions have been discontinued, have looked at interventions that were using techniques like commitment and feedback combined with goal setting [11,17,18,[21][22][23][24][25]. These techniques combined with a social element, such as peer feedback, public commitment, social marketing pressure, or community-based participation, appear to be even more promising in their ability to create persistent behaviors [21,22,24,[26][27][28][29], and are popular in public health initiatives for that reason [30]. As is suggested by many social psychology theories such as social identity pathway theory [31,32], perceived personal control [33], citizen participation [34], self-efficacy [35] and empowerment [36], the self-determined participatory element of these highlighted techniques, along with the engagement in communal action, may lead to a new self-definition that includes a sense of belonging, ownership, and responsibility to contribute to the collective group and act as a change agent.…”
Section: Behavior Durabilitymentioning
confidence: 99%